ANALYSIS OF MINERAL CONTENTS Ca, Mg, Fe AND Na IN NATURAL BENTONITE CLAY - Fathurrahmi Fathurrahmi (Jurnal Natural, 2012)
This research has been conducted to determine content of natural clay from bentonite in East Java area. There are two types of samples taken from the location, white and yellow clays. Samples were prepared to become the small pieces granulated, then were cleaned with aquadest, and were dried, respectively.After that, samples were re-minimized into 200 mesh in nanoparticles, re-cleaned and dried using oven at temperature 100-110 °Celsius. Ca, Fe, Mg and Na are contents in samples of bentonite Clay being determined by using Atom Absorption Spectrophotometer (AAS). Each part of the substance from yellow bentonite clays and white bentonite clays were measured and analysed its content with three times repetition. Natural-bentonite clays of Pacitan from East Java contained the minerals Ca, Mg, Fe and Na with mean values of the gratuity Ca 0.0127 % Mg 0.24655 %, Fe 0.56178 %, and Na 0.14122 % for yellow bentonite clays (A). White bentonite clays (B) consisted of minerals Fe, Mg, Na, and Ca with mean values of gratuity Ca 0.01856 %, Mg 0.30067 %, Fe 0.61235 %, and Na 0.1608%, respectively.